(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
The aim of the paper is to review the different research manuscripts on wrap faced embankment. Wrap faced embankment is basically a sand embankment wrapped around by geotextile layers as a steep embankment. This wrap-faced embankment is filled with different characteristics of sand. In this research, the wrap faced embankment is model by reduce scale in BUET Geotechnical Lab. The shaking table test machine was used to induce earthquake and wave action. The fifteen sensors have been placed in the wrap faced embankment and clay soil layer which was discussion on Hore et al. 2022. The different soil characteristics like accelerations, displacement, pore water pressure and strain has been analyzed in this research. This embankment showed better response to the earthquakes and wave action means stable to seismic and wave action. The results of the research have also been verified by numerical analysis by PLAXIS 3D software. Without knowing the characteristics of the wrap faced embankment during the earthquake, it is impossible to build this type earthquake/ wave resisting embankment. The dynamic behavior of wrap faced embankment on soft soil in Bangladesh has been invented by the Hore’s research. Now, it is possible to design and construction of earthquake/ wave resistance wrap faced embankment on soft Bangladeshi soil.